Peace be upon you: the story of Muslim, Christian, and Jewish coexistence - Karabell, Zachary (Alfred A. Knopf, 2007)
Includes information on Abbasid caliphate, Afghanistan, al Qaeda, Alexandria, Andalusia, Antioch, Arabic language, Armenians, Baghdad, Balkans, Beirut, Berbers, Byzantine Empire, Cairo, Christianity, Christians, Constantinople, Cordoba, Crusades, Damascus, Egypt, England, Europe, Fatimid dynasty, France, Franks, Greek Orthodox Church, ancient Greeks, Habsburgs, Caliph Harun al-Rashid, Hebrew language, Heraclius (Byzantine Emperor), Hezbollah, Holy Land, Hospitallers, Sharif Husayn ibn Ali, Iberian Peninsula, India, Iran, Iraq, Islam, Israel, Istanbul, Janissaries, Jerusalem, Jesus Christ, Jews, jihad, Judaism, Latin language, Lebanon, Moses Maimonides, Maronite Christian Church, Mecca, Medina, Mediterranean Sea, Sultan Mehmed II, monks, monasteries, Morocco, Muhammad ibn Abdullah (Prophet), Muslims, mysticism, nationalism, North Africa, Ottoman Empire, Pakistan, Palestine, Paris, People of the Book, People of the Pact, Persia, poetry, Quran (Koran), Quraysh tribe, reform movements, Roman Catholic Church, Rome, Russia, Saladin, Salonica, Seljuk dynasty, September 11, 2001 terrorist attacks, Spain, sultan Suleyman I, Syria, Templars, Torah, Turkey, Muhammad ibn Abd al-Wahhab, World War I, World War II, Zionism, Zoroastrians, etc